The Chemistry of CO2 and TiO2 From Breathing Minerals to Life on Mars - Civiš, Svatopluk; Ferus, Martin; Knížek, Antonín (SpringerBriefs in Molecular Science, 2019)
This book provides a comprehensive overview of the chemistry of CO2 in relation to surface interactions and photocatalytic transformation by UV radiation. The first part deals with the modelling of an anatase surface, its interaction with CO2, and the spontaneous exchange of oxygen atoms between the gas and solid phases. The book then naturally transitions to the photocatalytic reduction of CO2, achieved by adding UV radiation and traces of water to the experimental system, to produce methane and CO. This photocatalytic reduction is explained in detail and the implications for planetary chemistry (specifically concerning Mars), as well as Earth's atmospheric chemistry and global warming, are discussed.